The underground cult structure Sultan-epe on the Tupkaragan peninsula - Kalmenov, Мурат; Bizhanova , Алия; Zhalekenova, Гульбарам (Turkic Studies Journal, 2025)
This article examines the archaeological and architectural features of the Sultan-Epe underground mosque, which is located on the Tupkaragan peninsula in the Mangystau region of Kazakhstan. The region's territory is distinguished by a high concentration of historical and architectural monuments, shaped by its unique physical, geographical, and historical conditions. The abundance of rocks suitable for artistic processing played a key role in the development of stone-cutting traditions among the indigenous population of Mangystau. These traditions are marked by both high aesthetic and technological standards. The availability of these materials has led to the widespread use of local stone in construction, significantly reducing the reliance on brick production. Since ancient times, the peninsula's main building material has been limestone-shell rock, which is easily quarried and treatable. Despite its apparent fragility, this material retains its original shape and structural integrity over time. Consequently, many limestone structures have been preserved much better than buildings made of other materials, which have lost their original appearance over the centuries. A distinctive place within the region’s heritage is occupied by its underground architectural monuments, which is represented by religious structures that have been carved into rock formations below the surface. This tradition is believed to have originated in the early Middle Ages. To date, more than twenty such structures are known, characterized by a variety of designs and architectural styles. Among the earliest and most significant examples of this type is the Sultan-yepe underground mosque. This unique structure was created within a shallow channel formed by the erosive activity of floodwaters. The channel cuts through a rock formation approximately 2 metres thick, which is covered by marl clay belonging to the region's Neogene deposits. These geological charecteristics played a desicive role in shaping the architectural configuration of the monument and contributed to its long-term preservation. Archaeological investigations of the site were conducted in 2003 under the supervision of A.E. Astafiev and M.D. Kalmenov. The survey clarified key structural characteristics, identified elements of internal layout, and documented materials related to the long-term functioning of the cult complex. In 2005, restoration work was carried out to maintain its current condition and ensure its continued preservation. The Sultan-epe underground mosque is one of the most significant monuments within the architectural and archaeological heritage of Mangystau. It is distinguished by its exceptional state of preservation and considerable scientific value. Studying it contributes to a deeper understanding of the formation processes of the regional architectural tradition as well as the religious and cultural practices of the ancient communities that inhabited the thу peninsula.